The Effect of Dry Needling on Suprapatellar Tendonitis: A Case Report - Shahbazi, Majid (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2023)
Background Patellar tendinitis is common in jumping sports. Pain from patellar tendinopathy is challenging to manage. Dry needling as a stand-alone treatment for tendinopathy is supported. To our knowledge, dry needling has never been used alone. This case report depicts dry needling on the proximal patellar pole.Case description A 43-year-old male presented with left suprapatellar tendinitis. He was injured four months before beginning dry needling while playing futsal without warming up. The superior pole of the patellar was tender to palpation and caused moderate pain. At 20 degrees of knee flexion, discomfort began during double leg squats. The Clarke’s Sign, Eccentric Step, and Step Up tests showed positive results. The patient received five sessions of DN at the proximal pole of the patella twice weekly. This study’s primary outcomes were the numeric pain rating scale (NPRS), the Kujala Anterior Knee Pain Scale (AKPS), the global rating of change scale (GRC), and the angle of knee flexion during the squat. The researcher collected data at the five stages.Outcomes The patient’s primary outcome measures improved after three weeks of DN and three months of follow-up. The NPRS showed a reduction in pain, while the AKPS demonstrated a decrease in disability.Conclusion The successful treatment of a patient with suprapatellar tendinopathy utilizing DN is possibly described for the first time in this case report. This study demonstrated the efficacy of dry needling as a first-line treatment for managing chronic tendinopathy with a history of trauma.
Keywords: suprapatellar tendonitis; dry needling; jumper knee; tendinopathy